Restructuring the Cellular Responses: Connecting Microbial Intervention With Ecological Fitness and Adaptiveness to the Maize (Zea mays L.) Grown in Saline–Sodic Soil - Singh, Shailendra; Singh, Udai B.; Trivdi, Mala; Malviya, Deepti; Sahu, Pramod K.; Roy, Manish; Sharma, Pawan K.; Singh, Harsh V.; Manna, M. C.; Saxena, Anil K. (Frontiers in Microbiology, 2021)
Salt stress hampers plant growth and development. It is now becoming one of the most important threats to agricultural productivity. Rhizosphere microorganisms play key roles in modulating cellular responses and enable plant tolerance to salt stress but the detailed mechanisms of how this occur need in-depth investigation. The present study elucidated the microbe-mediated re-structuring the cellular responses lead to ecological fitness and adoptiveness to the maize (Zea mays L.) grown in saline sodic soil. In this study, effects of seed biopriming on different growth parameters were recorded. Soil biochemical and enzymatic analyses were performed. The activity and gene expression of ZmHKT-1, NHX1 and antioxidant enzymes were studied. The expression of genes related to lateral root development and root architecture were also carried out. Seeds bioprimed with selected strains individually or in combination have been shown to confer better seed germination and vigour in the plant grown at 30 days of sowing. Results indicated that plants treated with consortium of three strains induced early production of adventitious roots in maize compared to plants primed with single strains and untreated control which was further confirmed by assessing the transcript level of ZmHO-1, ZmGSL-1 and ZmGSL-3 genes using qPCR approach. The uptake and translocation of Na+, K+ and Ca2+ significantly varied in the plants treated with bioagents in consortium. qRT-PCR analysis also revealed that the ZmHKT-1 expression levels varied significantly in the maize root upon inoculation and showed manifold increase in the plants bioprimed with all the three strains in combination. Further, the activity and gene expression levels of antioxidant enzymes showed significantly higher in the leaves of maize subjected seed biopriming with bioagents individually or in combination. Our research indicated that ZmHKT-1 expression could effectively enhance salt tolerance by maintaining an optimal Na+/K+ balance and increasing the antioxidant activity that keeps reactive oxygen species (ROS) at a low accumulation level. Interestingly, up-regulation of ZmHKT-1, ZmHO-1, ZmGSL-1 and ZmGSL-3 and genes encoding antioxidant regulate the cellular responses which could effectively enhance the adoptiveness and ultimately leads to better plant growth, and grain production in the maize crop grown in saline sodic soil.